In vitro comparative cytotoxicity study of aminated polystyrene, zinc oxide and silver nanoparticles on a cervical cancer cell line. (2nd January 2019) - Sharma, Akash; Gorey, Brian; Casey, Alan
Abstract: Nanoparticles use in nano-biotechnology applications have increased significantly with Aminated polystyrene amine (AmPs NP), Zinc oxide (ZnO NP), and Silver (Ag NP) nanoparticles utilized in wide variety of consumer products. This has presented a number of concerns due to their increased exposure risks and associated toxicity on living systems. Changes in the structural and physicochemical properties of nanoparticles can lead to changes in biological activities. This study investigates, compares, and contrasts the potential toxicity of AmPs, ZnO and Ag NPs on an in vitro model (HeLa cells) and assesses the associated mechanism for their corresponding cytotoxicity relative to the surface material. It was noted that NPs exposure attributed to the reduction in cell viability and high-level induction of oxidative stress. All three test particles were noted to induce ROS to varying degrees which is irrespective of the attached surface group. Cell cycle analysis indicated a G2/M phase cell arrest, with the corresponding reduction in G0/G1 and S phase cells resulting in caspase-mediated apoptotic cell death. These findings suggest that all three NPs resulted in the decrease in cell viability, increase intracellular ROS production, induce cell cycle arrest at the G2/M phase and finally result in cell death by caspase-mediated apoptosis, which is irrespective of their differences in physiochemical properties and attached surface groups.